Characterization of Spermidine Synthase (SPDS) Gene and RNA−Seq Based Identification of Spermidine (SPD) and Spermine (SPM) Involvement in Improving High Temperature Stress Tolerance in Gracilariopsis lemaneiformis (Rhodophyta) - Shixia Liu; Jun Zhang; Xue Sun; Nianjun Xu (Frontiers in Marine Science, 2022)
Gracilariopsis lemaneiformis , an important commercial red macroalga, is facing significant impacts from global warming, which limits algal growth and yield in China. Polyamines (PAs), spermidine (SPD) and spermine (SPM), are ubiquitous polycations important for growth and environmental stress responses including high temperature (HT) tolerance. Spermidine synthase ( SPDS ) gene is one of the important genes in higher PA biosynthesis, which plays critical roles in HT stress response. Here, we isolated an SPDS gene from G. lemaneiformis and further analyzed its phylogenetic tree, subcellular localization, and gene expression patterns under stress conditions. Meanwhile, supplemented with SPD and SPM were used to study the effects of PAs on HT tolerance in G. lemaneiformis . It showed exogenous 0.5 mM SPD and SPM, respectively, remarkably improved the algal relative growth rate (RGR) compared to those in the CK treatment groups under HT conditions. In addition, they both significantly elevated the activities of antioxidant enzymes and significantly upregulated the expression of genes encoding antioxidant enzymes, triggered transcription factors (TFs) signaling, and improved the expression of genes encoding small heat shock proteins (sHSP20s) during HT stress. Moreover, exogenous PA also enhanced the expression of genes involved in pyruvate metabolism, ascorbate and aldarate metabolism, and nucleotide excision repair in G. lemaneiformis , which helped to maintain better energy supply, redox homeostasis, and genome integrity under HT stress. Taken together, these data provided valuable information for functional characterization of specific gene in endogenous PA synthesis and uncovered the importance of exogenous PAs in promoting algae adaptation to HT stress.